First records of Composetia, Eunereis and Nectoneanthes (Annelida: Nereididae) from Taiwan, with descriptions of two new species - Hsueh, Pan-Wen (Zootaxa, 2018)
Three species of nereidids collected from various ecological surveys conducted on coasts of west central and northeastern of Taiwan are studied. Each species represents a genus in the subfamily Nereidinae Blainville, 1818 not previously reported from Taiwan: Composetia Hartmann-Schröder, 1985, Eunereis Malmgren, 1865 and Nectoneanthes Sato, 2013. Composetia budaiensis n. sp. can be distinguished from congeners by having 2–5 and 17–27 paragnaths on Areas I & III of the pharynx, respectively. Eunereis shichengensis n. sp. differs from congeners by having one shield-shaped bar on Area VI of the pharynx. The generic diagnosis of Eunereis is emended slightly to include short neuropodial heterogomph falcigers in E. shichengensis n. sp. and three other congeners. Nectoneanthes species examined in the present study showed a continuous broad band of numerous paragnaths on the oral ring of the pharynx, which agrees with the unique character of N. uchiwa Sato, 2013 and represents the first record of the species for Taiwan. A key to all known species to Eunereis are provided.